Run for the hills : [large type] a novel - Wilson, Kevin, 1978- (Thorndike Press, 2025)
Ever since her dad left them twenty years ago, it's been just Madeline Hill and her mom on their farm in Tennessee. Then one day Reuben Hill pulls up and informs Madeline that he believes she's his half-sister. Reuben has hired a detective to track down their father and a string of other half siblings. And he wants Mad to join him for the craziest kind of road trip imaginable to find them all. As Mad and Rube -- and eventually the others -- share stories of their father, they question what he was looking for with every new incarnation. Who are they to one another? What kind of man will they find? And how will these new relationships change Mad's life on the farm?